Mild form of oculocutaneous albinism type 1: phenotypic analysis of compound heterozygous patients with the R402Q variant of the TYR gene. Issue 9 (24th November 2018) - Monfermé, Solene; Lasseaux, Eulalie; Duncombe-Poulet, Catherine; Hamel, Christian; Defoort-Dhellemmes, Sabine; Drumare, Isabelle; Zanlonghi, Xavier; Dollfus, Hélène; Perdomo, Yaurama; Bonneau, Dominique; Korobelnik, Jean-François; Plaisant, Claudio; et al.
Abstract : Aim: Oculocutaneous albinism type 1 (OCA1) is due to TYR mutations. c.1205G>A/p.Arg402Gln (R402Q) is a thermosensitive variant of the TYR gene that has been reported to be responsible for mild forms of OCA1. The aim of our study was to define the phenotype associated with this variant. Methods: In our retrospective series, among 268 patients diagnosed with OCA1, 122 (45.5%) harboured one pathogenic variant of TYR, and the R402Q variant ensured to be in trans by segregation analysis in 69 patients (25.7%), constituting the 'R402Q-OCA1' group. 146 patients harboured two pathogenic variants of the TYR gene other than R402Q. Clinical records were available for 119 of them, constituting the 'Classical-OCA1' group. Results: Most R402Q-OCA1 patients presented with white or yellow-white hair at birth (71.43%), blond hair later (46.97%), a light phototype but with residual pigmentation (69.64%), and blue eyes (76.56%). Their pigmentation was significantly higher than in the classical-OCA1 group. All patients from the R402Q-OCA1 group presented with ocular features of albinism. However the prevalence of photophobia (78.13%) and iris transillumination (83.87%) and the severity scores of iris transillumination, retinal hypopigmentation and foveal hypoplasia were lower in the R402Q-OCA1 group. Visual acuity was higher in the R402Q-OCA1 group (0.38±0.21 logarithm of the minimum angle of resolution vs 0.76±0.24). Investigations concerning a possible additive effect of the c.575C>A/p.Ser192 (S192Y) variant of TYR in cis with R402Q, suggested by others, showed no significant impact on the phenotype. Conclusion: The R402Q variant leads to variable but generally mild forms of albinism whose less typical presentation may lead to underdiagnosis.